Do loans harm? The Effect of IMF Programs on Inequality - N. Gilbert; Brigitte Unger (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2009)
IMF programs consist of granting loans, and of conditionality that countries have to follow in order to qualify for them. The paper uses a pooled time-series cross section analysis, covering 98 countries over the period 1970-2000 in order to find out which effect IMF programs have on the personal and wage income distribution of the grant receiving country. Similar to findings on growth (Dreher 2006), IMF programs have also a negative impact on income. This is due mainly to conditionality, whereas the amount of loans granted does not seem to harm.
Keywords: 330; developing countries; inequality; pooled regression; IMF programs; loans and conditionality